2014
DOI: 10.1063/1.4873710
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating binding mechanisms of an intrinsically disordered protein via a multi-state coarse-grained model

Abstract: Many proteins undergo a conformational transition upon binding to their cognate binding partner, with intrinsically disordered proteins (IDPs) providing an extreme example in which a folding transition occurs. However, it is often not clear whether this occurs via an "induced fit" or "conformational selection" mechanism, or via some intermediate scenario. In the first case, transient encounters with the binding partner favour transitions to the bound structure before the two proteins dissociate, while in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 89 publications
1
54
0
1
Order By: Relevance
“…Zuckerman 30 has used a united residue model with a structure-based potential, i.e., the Go model 25 with double native structures to probe the conformational phase space of Calmodulin. Knott and Best 31 have used a multi-state coarse-grained description, somewhat similar to the double Go model, to analyze the binding mechanism of an intrinsically disordered protein. These studies [27][28][29][30][31] involve protein structures in devising the models and are very useful in examining the structural evolutions spanning over a large time scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zuckerman 30 has used a united residue model with a structure-based potential, i.e., the Go model 25 with double native structures to probe the conformational phase space of Calmodulin. Knott and Best 31 have used a multi-state coarse-grained description, somewhat similar to the double Go model, to analyze the binding mechanism of an intrinsically disordered protein. These studies [27][28][29][30][31] involve protein structures in devising the models and are very useful in examining the structural evolutions spanning over a large time scale.…”
Section: Introductionmentioning
confidence: 99%
“…Knott and Best 31 have used a multi-state coarse-grained description, somewhat similar to the double Go model, to analyze the binding mechanism of an intrinsically disordered protein. These studies [27][28][29][30][31] involve protein structures in devising the models and are very useful in examining the structural evolutions spanning over a large time scale. It is not common to see such a detailed analysis of fractality 27 and structure factors 28, 29 that span multiple scales in protein modeling, particularly in crowded systems.…”
Section: Introductionmentioning
confidence: 99%
“…These simulations argue that the IRF-3 bound conformation is only rarely accessible from the unbound state, indicating that the presence of that binding partner may be necessary for NCBD to sample that state (58). A separate molecular dynamics simulation study of NCBD binding to its interaction domain on the human activator for thyroid hormone and retinoid receptors protein (ACTR) or IRF-3 indicated that NCBD samples its bound conformation for each of these partners much more readily in the presence of that partner than in its absence (59).…”
Section: Ncbdmentioning
confidence: 99%
“…4). Molecular dynamics simulations of the unbound state have shown that NCBD samples a wide variety of conformations characterized by different orientations and lengths of its helices (58,59). Long time-scale simulations indicated that NCBD samples conformations similar to each known bound structure at low rates.…”
Section: Ncbdmentioning
confidence: 99%
“…They found that NCBD binding to either partner occurs via an induced fit mechanism. 21 Gianni et al describe a kinetic method which distinguishes induced fit from conformational selection and relies on an observation of the rate constant for binding while varying the protein and ligand concentrations in separate experiments. 22 Using statistical mechanics, calorimetry, and NMR spectroscopy, Krieger et al showed conformational selection in the binding of a fragment of the IDP Gab2 to the growth factor receptor-bound protein 2 (Grb2).…”
mentioning
confidence: 99%